2015
DOI: 10.1017/s0022149x15000620
|View full text |Cite
|
Sign up to set email alerts
|

The present situation of echinococcoses in Mongolia

Abstract: This review presents the historical and current situation of echinococcoses in Mongolia. Since the collapse of the Soviet Union in 1991, Mongolia's health surveillance infrastructure has been very poor, especially as it pertains to chronic diseases, including neglected zoonotic diseases (NZDs). Although there is anecdotal evidence of people dying from hepatic disease due to infection with the larval stage of Echinococcus spp., there are very few published reports. All confirmed cases of echinococcoses in Mongo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 86 publications
(179 reference statements)
0
21
0
Order By: Relevance
“…Based on this prevalence of 4.7%, a much higher national prevalence can be estimated as shown in Table 3. In Mongolia, AE is less common than CE (Ito and Budke, 2015). Echinococcus multilocularis has been documented in wild canids (red foxes and wolves) in northern Mongolia .…”
Section: 2 Infections In Animalsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on this prevalence of 4.7%, a much higher national prevalence can be estimated as shown in Table 3. In Mongolia, AE is less common than CE (Ito and Budke, 2015). Echinococcus multilocularis has been documented in wild canids (red foxes and wolves) in northern Mongolia .…”
Section: 2 Infections In Animalsmentioning
confidence: 99%
“…Apart from one infected vole (Microtus limnophilus) from Khovd Province (Gardner et al, 2013) (Ito and Budke, 2015). So far five cases of AE have been documented in four provinces, mainly in the northwest of Mongolia (Ito and Budke, 2015). Molecular studies from metacestodes of three AE patients revealed both Asian and the Mongolian E. multilocularis haplotypes (Ito et al, 2010).…”
Section: 2 Infections In Animalsmentioning
confidence: 99%
See 3 more Smart Citations